A laboratory scale research to obtain environmentally safe effluent from Final Waste Disposal Site leachate in Galuga owned by Regional Government of Bogor City was conducted from July 2006 through to April 2007. The experiment of production tolerable threshold effluent was carried out by aerating the leachate in 4 different aeration rates (0, 10, 30 and 70 liters/minute). The research found that the most effective method to reduce pollutant was aerating at the rate of 70 liters/minutes. Howev - Nurhasanah .; Latifah K. Darusman; Surjono Hadi Sutjahjo; Bibiana Widiati Lay (Forum Pasca Sarjana, 2011)
A laboratory scale research to obtain environmentally safe effluent from Final Waste Disposal Site leachate in Galuga owned by Regional Government of Bogor City was conducted from July 2006 through to April 2007. The experiment of production tolerable threshold effluent was carried out by aerating the leachate in 4 different aeration rates (0, 10, 30 and 70 liters/minute). The research found that the most effective method to reduce pollutant was aerating at the rate of 70 liters/minutes. However, only some of pollutant (Cu, Zn, Pb and E.coli) can be reduced until below tolerable threshold. Keywords: effluent, leachate, tolerable threshold